Comparison of the quality of poplar lumber in the upper, middle and lower rows of wood drying kiln - Sohrab Rahimi (Regional Information Center for Science and Technology (RICeST), 2011)
Poplar lumbers with nominal thickness of 5 cm from Taleghan region, located in west of Karaj were dried under three different schedules including T8-F4 (recommended schedule by F.P.L for poplar), T8-F5 and T9-F4. The purpose of this research was to study the effects of the kiln’s rows (upper, middle, lower) on the quality of the dried boards. Dry bulb temperatures for the schedules were adjusted at 54, 54 and 60 °C, while the final temperatures were adjusted at 82, 82 and 71 °C, respectively. The severity of warping, internal checking and surface checking in kiln dried lumbers were measured and analyzed. The results indicated that the boards in upper, middle and lower rows of the kiln, in all three schedules, did not have any significant difference in 95% confidence interval. Also, the final moisture content of the boards in all three rows and all three schedules were in acceptable quality.